2020
DOI: 10.1186/s12957-020-1802-6
|View full text |Cite
|
Sign up to set email alerts
|

How does lymph node yield affect survival outcomes of stage I and II colon cancer?

Abstract: Background: According to the American Joint Committee on Cancer staging for cancer of the colon, a minimum of 12 lymph nodes (LN) has to be sampled for accurate staging. This has bearing on the long-term prognosis and the need for adjuvant chemotherapy. The aim of this study was to revisit the association of lymph node yield and the long-term survival in patients with stages I and II, i.e. node-negative, colon cancer. Method: Consecutive patients who underwent elective or emergency curative resections for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Lymph node yield (LNY), defined as the number of lymph nodes retrieved following specimen dissection, [ 136 ] is a strong prognostic factor, particularly in non-metastatic CRC [ 38 , 39 , 41 , 212 , 213 , 214 ]. Inadequate LNY may be a factor in decision-making for adjuvant chemotherapy [ 1 , 7 ].…”
Section: Pathological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymph node yield (LNY), defined as the number of lymph nodes retrieved following specimen dissection, [ 136 ] is a strong prognostic factor, particularly in non-metastatic CRC [ 38 , 39 , 41 , 212 , 213 , 214 ]. Inadequate LNY may be a factor in decision-making for adjuvant chemotherapy [ 1 , 7 ].…”
Section: Pathological Featuresmentioning
confidence: 99%
“…Several studies have demonstrated that a higher LNY, regardless of status (positive or negative) is associated with improved OS, DFS, and reduced risk of recurrence [ 39 , 41 , 215 , 216 ]. LNY has been established as an important prognostic factor in stage II and III colorectal cancer [ 39 , 41 , 212 , 214 ] and while its utility in stage I CRC is less clear [ 214 ], emerging evidence suggests that there is a prognostic association in stage I CRC [ 38 , 39 , 213 ].…”
Section: Pathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher lymph node yield may improve overall and disease-free survival, especially in patients with stage II colon cancer. 1,2 A risk of understaging the disease and withholding necessary chemotherapy is present when a small number of lymph nodes is sampled. 3,4 The minimum number of lymph nodes to be examined is controversial, but 12 has been suggested as a standard for an adequate excision.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 There is a high variability on reported lymph node yield between centres, but a significant number of colorectal cancer specimens remain that fail to reach this threshold. 1,7,8 Many factors may affect the nodal yield, such as age, gender, location of the tumour, tumour stage and body mass index, but the two modifiable ones are the extent of lymphadenectomy and the quality of the pathological examination. [9][10][11][12] The standard approach to identify lymph nodes is through manual palpation of the specimen; however, this may result in some lymph nodes being missed, particularly those smaller than 5 mm.…”
Section: Introductionmentioning
confidence: 99%